PENGARUH RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEMEN MILIK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 3(TIGA) BULAN - Agustin, Jilveira; Kartika, Chandra (Develop, 2019)
The purpose of this research is to know the influence of return on equity against the share price on the cement companies belonging to STATE OWNED ENTERPRISES (BUMN) registered in busra effect Indonesia. To know the influence of earning per share on the company's share price against the cement property of STATE-OWNED ENTERPRISES listed dibursa the effect of Indonesia. In this study the author determines the sample used cement companies belonging to STATE-OWNED ENTERPRISES (BUMN). 2. Methods of analysis used in this study i.e. multiple linear analysis. Research results Return On Equity (ROE) and Earning Per Share (EPS) to simultaneously effect significantly to stock price and Return On Equity (ROE) influential partially against the stock price and Earning Per Share (EPS) was influential in partial against stock prices